The Incidence of Ischemic Cholecystitis after Prophylactic Cystic Artery Embolization: A Single-Center Retrospective Study - Benjamin J. Walker; Michael Lung; Hanin Lataifeh; Aditi Patel; Ibrahim Abukhiran; Mohammad Amarneh (The Arab Journal of Interventional Radiology, 2023)
Background Prophylactic cystic artery embolization (CAE) is used to prevent radiation cholecystitis in patients undergoing transarterial radioembolization (TARE), but the incidence of ischemic cholecystitis following CAE remains unclear.